ANALISIS NILAI ESTETIS PADA NOVEL BUMI MANUSIA KARYA PRAMOEDYA ANANTA NOER - Syarah Ihsani; Yoyuti Sonata Capah (FKIP, Universitas Palangka Raya, 2023)
The novel, Bumi Manusia, tells the story of the socio-cultural life of the Javanese people during the Dutch colonial era. This study aims to describe the aesthetic cultural values contained in the novelBumi Manusia by Pramoedya Ananta Toer and the implications of these values for Indonesian language learning in high school. They cover (1) human life;(2) the value of the nature of human relations with others; (3) the value of the nature of human work (4) the value of the nature of man and the universe (5) the value of the nature of man in relation to time and space. This research applies the analysis-descriptive method. The data taken to support this research are quotes found in the novel Bumi Manusia, which refers to the Javanese cultural values.. The data analysis technique used is distributional analysis technique, namely the selection of data based on certain categories from a programmatic perspective in accordance with the natural characteristics of the research data. The results showed that the Javanese cultural values contained in the novel Bumi Manusia are values of sincerity, simplicity, mutual respect, harmony with the universe, and patience. The implication of this value for learning Indonesian in high school is that students are able to understand, translate, and implement the messages or values contained in the novel Bumi Manusia for the life of their surroundings.